Clinacanthus nutans crude polysaccharide extract as a green platform for microwave-assisted synthesis of silver nanoparticles: optimization, characterization, and evaluation of bioactivities - Devasvaran, Kogilavanee; Alallam, Batoul; Lee, Carmen; Yong, Yoke Keong; Lim, Vuanghao (Elsevier, 2024)
Clinacanthus nutans (C. nutans) is a plant in tropical Asia with proven biological activities. The optimized extraction method of C. nutans crude polysaccharide (CNP) uses water in the presence of an ultrasound-assisted mechanical method (UL_CNP). However, the use of UL_CNP for the synthesis and optimization of silver nanoparticles (AgNP), particularly their anticancer and photocatalytic properties, remains unexplored. Hence, this research aimed to employ a green method using UL_CNP and silver nitrate to produce AgNP (UL_AgNP) with a small size and assess its potential toxicity, anticancer, and photocatalytic activities. The synthesis condition was optimized using the Box–Behnken design method. The synthesized UL_AgNP showed the surface plasmon resonance peak at 458 nm. The optimized synthesis condition produced spherically shaped UL_AgNP with a size of 5.21 ± 1.92 nm and a zeta potential of −26.33 ± 0.93 mV. An X-ray diffraction analysis exhibited intense Bragg's reflection peaks at (111), (200), (220), and (311), having a face-centered cubic structure of AgNP. Attenuated total reflectance-Fourier-transform infrared spectroscopy and energy-dispersive X-ray spectroscopy further confirmed the presence of silver in the synthesized UL_AgNP. The brine shrimp lethality test of UL_AgNP reported a lethal concentration 50 value of <7.8 μg/mL after 24 h. The UL_AgNP exhibited antiproliferative activity against MCF-7 cells with a half-maximal inhibitory concentration value of 4.96 ± 0.31 μg/mL by inducing S-phase cell cycle arrest, apoptotic effect, and reduction of cell migration. Furthermore, UL_AgNP proved its efficient photocatalytic activity against methylene blue dye (50.22 % ± 0.06 %, after 10 min at a concentration of 50 μg/mL). Therefore, the UL_AgNP exhibited promising antiproliferative activity against MCF-7 cells, highlighting their potential as a therapeutic agent. Further investigations are needed to elucidate the precise mechanism of their action.